PERAN UNITED NATIONS HIGH COMMISSIONER FOR REFUGEES DALAM MENANGANI PENGUNGSI SURIAH DI TURKI TAHUN 2011-2014 - Suhartono, Bambang (Global and Policy Journal of International Relations, 2017)
ABSTRACTThis study aims to determine the extent to which the role of UNHCR in dealing with Syrian refugees in Turkey. UNHCR as an international organization with a special mandate in the handling of refugees globally, especially Syrian refugees, has an important role as humanitarian assistance and in capacity building. In addition, UNHCR also undertakes a variety of strategic cooperation with several other local / international organizations such as UNICEF, IOM, WFP, and AFAD. The role undertaken by UNHCR is urgently needed and important for Syrian refugees in Turkey. Providing protection for their safety and human rights in other countries must also be guaranteed for their sustainability to avoid uncomfortable actions from the country where the refugees are located. In addition, the cooperation undertaken by UNHCR with other local / international organizations can have a direct positive impact on refugees through the large number of humanitarian and humanitarian assistance and monitoring of the safety of Syrian refugees in Turkey.Keywords: International Organization, Role of International Organization, UNHCR, AFAD, Syrian RefugeesDOI : https://doi.org/10.33005/jgp.v5i01.1897